The effect of calcineurin inhibitors in the treatment of IgA nephropathy: A systematic review and meta-analysis (PRISMA) - Peng, Wei (Medicine (Baltimore), 2016)
BACKGROUND: Immunoglobin A nephropathy (IgAN), the most prevalent form of primary glomerulonephritis, represents the leading cause of kidney failure among East Asian populations. Immunosuppressive treatment regimen, except for a 6-month trial of corticosteroids, has not been approved by the KDIGO guideline yet. Specific and effective treatment is still lacking. We decided to evaluate the efficacy and safety of the calcineurin inhibitors (CNIs) in the treatment of IgAN. METHODS: Database from the Cochrane library, PubMed, Embase, CBM, CNKI, and CENTRAL databases were searched and reviewed up to March 2016. Literature was screened by 2 independent reviewers accordingly. Clinical trials were analyzed using Stata 12.0. RESULTS: Five random control trials and 2 nonrandomized concurrent control trials were selected and included in this study according to our inclusion and exclusion criteria. The rates of complete remission in patients with IgAN were significantly increased in the group of CNIs (RR 1.56, P = 0.002). No statistical difference was observed in the rates of partial remission, or response between the CNIs and steroids alone. Additionally, CNIs resulted in a significant reduction in urinary protein (WMD 0.34, P = 0.002) and increase in serum albumin level (WMD 1.89, P = 0.013). No differences were found in the serum creatinine, estimated glomerular filtration rate, and rates of adverse effects including infection, hyperglycemia, and liver dysfunction. CONCLUSION: With present evidence, CNIs may be promising immunosuppressive agents for IgAN in future. However, large, long-term, multicenter trials are required to confirm our findings.